Aktivitas Sitotoksik Ekstrak Etanolik Rimpang Temu Kunci (Boesenbergia pandurata) Terhadap Sel Kanker Serviks HeLa dan Sel Kanker Kolon WiDr - Feby Handoko, Fransiscus; Ayu Maruti, Astrid; Rivanti, Erlina; Dewi Pamungkas Putri, Dyaningtyas; Meiyanto, Edy (Lembaga Penelitian Universitas YARSI, 2011)
Temu kunci (Boesenbergia pandurata) rhizome showed cytotoxic effect against T47D breast cancer cell line. It contains Panduratin, a chalcone compund, that has been investigated as chemopreventive agent. The exploration of extract of temu kuci as chemopreventive agent was expected to be an alternative for cancer therapy. The aim of this research was to determine the cytotoxic activities of ethanolic extract of temu kunci against HeLa cervix cancer and WiDr colon cancer cell line. The cytotoxic activities of ethanolic extract of temu kunci were tested using MTT assay against HeLa and WiDr cells. The IC50 values were obtained using linier regression equation. The ethanolic extract of temu kunci showed cytotoxic activities on HeLa cervix cancer and WiDr colon cancer cell lines with IC50 at 87 µg/mL and 76 µg/mL, respectively. Low IC50 values (100 µg/mL) showed that ethanolic extract of temu kunci is potential to be developed as chemoprevention agent on cervix cancer and colon cancer. However, its molecular mecahanism need to be explored.